PENANAMAN JIWA ENTREPENEURSHIP MAHASISWA SEMESTER 2 DIPLOMA 3 BAHASA INGGRIS, UNIVERSITAS JEMBER MELALUI MATA KULIAH WRITING I - Setiarini, Riskia; Kusumaningputri, Reni (Jurnal Pengembangan Pendidikan, 2010)
Abstract. The need for upgrading the D3 Bahasa Inggris students’interest and writing ability leads to an idea to implement a teaching design inorder to supply entrepreneurship skill to them through Writing I course.Concerning with it, this research is aiming at: 1) improving and increasing thebetter motivation change and entrepreneurship skill as a means to solveproblems in teaching and learning activity of Writing I for students of thesecond semester of D3 Bahasa Inggris, 2) becoming one of strategic steps toundertake for improving education service wholly, and 3) becoming as a meansfor skill development for both lecturers and students which is based on theneed to solve problems of Writing I learning especially for students of D3Bahasa Inggris. The design of this research is Classroom Action Research due tothe fact that it is based on a situational problem, occurring at the time ofconducting Writing I teaching. Apart from what has been mentioned, the proposedteaching design is for improving the teaching and learning quality as well asimproving the students’ study result. The result of this research shows that 14from the total number 15 students (more or less 93%) assume that this methodhas efficiency and ‘power to assist’ in Writing I teaching and learning, thatis improving the students’ writing ability. Twelve to fourteen students(86-99%) said that this method has a capability to give learning motivation interms of an effective interaction between lecturers-students as well asaffective support needed by the students. It means that this teaching design isquite appropriate to use as an alternative method in supplying entrepreneurshipskill through its output that is writing skill ability.Key words: Entrepreneurship, wrting 1, storybook for children